Social Struggles and Treatment Seeking Behaviors of Infertile Women among Different Classes in the Urban Areas of Bangladesh - Zaman, Athoy; Rahim, Rifatur; Nessa, Khaledun; Rouf, MA; Rahman, Farzana (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: Infertility is considered a taboo in the society of Bangladesh and is negated in reproductive health programs as well as in the research setting. Yet it is crucial and endemic for social and public health sectors. In Bangladesh, infertile women have to bear the drudgery of dishonor and shame because of their childlessness. The childless women have to shoulder most of the burden of ill-treatment for impotence regardless of who is at fault. Like other social stigmas, this also intersects across class, gender and setting barriers. Objective: The aim of the study is to understand the social struggles, stigmatization and treatment seeking behavior of infertile women of different classes in the urban context of Bangladesh. Methodology: A descriptive qualitative research methodology with in-depth interviews was used to collect data from 20 childless urban women aged between 18 to 45 years. They were urban residents for at least ten years and were aware of their infertile condition for at least one year. Results: The research results showed that childless women, irrespective of their class identities, always live with stigma, accusations and fear of abandonment in their personal lives. It also initiates an arena of violence. Many infertile women face physical and mental abuse due to their childlessness. The treatment seeking behaviors also vary based on financial conditions and the formality of the services among infertile women of different social classes. Conclusion: Infertility is a critical component of reproductive health. When a woman’s worth is measured by her reproductive functions, the childless woman faces humiliation and even abandonment. Attitude towards them is changed due to the societal norms and patriarchal social structures. This affects their treatment seeking behaviors as well. A proper understanding of the social condition of infertile women will facilitate the improved quality of women’s reproductive health care services. J Shaheed Suhrawardy Med Coll 2020; 12(2): 82-86